The impact of small scale irrigation on household food security: the case of Filtino and Godino Irrigation Schemes in Ada Liben District, East Shoa, Ethiopia - Tesfaye, A.; Bogale, A.; Namara, Regassa E. (2008)
Irrigated production is far from satisfactory in the country. The country's irrigation potential is estimated at 3.7 million hectare, of which only about 190,000 hectare (4.3 percent of the potential) is actually irrigated. The aim of this paper is to identify the impact of small-scale irrigation on household food security based on data obtained from 200 farmers in Ada Liben district of Ethiopia. Different studies revealed that access to reliable irrigation water can enable farmers to adopt new technologies and intensify cultivation, leading to increased productivity, overall higher production, and greater returns from farming. In the study area also about 70 percent of the irrigation users are food secure while only 20 percent of the non-users are found to be food secure. Access to irrigation enabled the sample households to grow crops more than once a year; to insure increased and stable production, income and consumption; and improve their food security status. The study concludes that small-scale irrigation is one of the viable solutions to secure household food needs in the study area but it did not eliminate the food insecurity problem.